(untitled) (Universal International Scientific Journal, 2026)
This article examines the priority aspects of using modern psychological mechanisms to awaken the creative potential and creative thinking of primary school students. The pedagogical and psychological foundations of expanding the scope of independent thinking of students in the modern education system are analyzed. It also describes ways to reveal children’s talents using interactive methods, problem-solving games and digital technologies in the lesson process, as well as methods for developing independent thinking and the ability to come up with unusual solutions. It is shown that awakening creativity in children is not only an educational but also an important factor in increasing their self-confidence.